Planlos durchs Praktikum? Zielorientierter Kompetenzerwerb in der schulpraktischen Ausbildung angehender Lehrpersonen - Krattenmacher, Samuel (Beiträge der Schweizer Bildungsforschung, 2014)
In the practical training of prospective teachers in schools, a goal-oriented acquisition of competence is to be aimed at. In particular, the consulting method of goal-oriented pedagogical coaching, with the three core elements of work relationship, goal definition skills and goal-oriented work, plays a central role and can contribute to the expansion of action competence. The author explains how.